My Brother’s Keeper, My Sister’s Neglector: A Critique and Explanation of Single-Sex Initiatives for Black Boys - Lane-Steele, Laura (Columbia Journal of Gender and Law, 2020)
The urgent problems facing Black boys and young men have triggered the proliferation of single-sex initiatives aimed at tackling these obstacles, namely public single-sex schools and programs inspired by President Obama’s My Brother’s Keeper initiative. Black girls have largely been left out of these initiatives despite facing many of the same barriers as Black boys and disadvantages of their own. This Article identifies, critiques, and explains this disproportionate intervention for Black boys. It argues that these single-sex initiatives are a poor policy tool for fighting racial oppression because (1) there is no evidence that these boys-only initiatives work to achieve their stated goals; (2) statistical gender gaps between Black boys and girls are not large enough to warrant disproportionate intervention; and (3) these initiatives have great potential to reify destructive aspects of dominant Black masculinity. It then employs critical race theory to explain how this current disproportionate intervention is part of a historically-based discourse that prioritizes Black men’s needs over those of Black women, casts Black men as “privileged victims” of racism, and seeks to restore patriarchy in the Black community. Finally, it predicts that these initiatives will continue to proliferate for two reasons. First, the current legal frameworks, specifically Title IX and the Equal Protection Clause, do not necessarily prevent the increasing disproportionality of these initiatives and the resulting unfairness to Black girls. Second, there is insufficient political will to halt the expansion of these initiatives—they face little to no political opposition, even from politicians on the Left who claim to champion gender equity.